Electrodeposited nanometer-size IrO2/Ti electrodes with 0.3 mg IrO2 cm−2 for sludge dewatering electrolysers. (1st March 2018) - Zhang, Yanlin; Cao, Manman; Lv, Hang; Wei, Jucai; Gu, Yueyuan; Liu, Daoguang; Zhang, Wenbiao; Ryan, Mary P.; Wu, Xu
Abstract: Dewatering electrolysers are useful devices for efficiently reducing the water content of sewage sludge to <60%. High noble metal loadings of the dimensionally stable anodes, e.g. IrO2 -coated titanium electrodes, cause a main cost of such devices. In this paper, iridium oxide (IrO2 ) coatings are electrodeposited on titanium to prepare the anodes. The loading amounts and morphologies of these IrO2 deposits are varied by tuning parameters such as the electrodeposition potential, concentration of Iridium salts, and deposition time. An amorphous iridium oxide was obtained after electrodeposition, which was successively calcined at 500 °C. In the sludge electrodewatering test, the electrodeposited IrO2 /Ti electrodes with an ultra small IrO2 loading level (0.3 mg cm −2 ) shows acceptable performance, i.e. the water content of sludges in the electrodewatering system can be reduced to about 60 wt% at 25 V and 55% at 35 V.